A study on the utilization of popular culture materials in teaching library and information science students - Romero, Stephen John C.; Buenrostro, Iyra S. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2008)
This study was done to find out the extent by the usage by the UP School of Library and Information Studies professors of popular culture materials in teaching LIS subjects and what the students' responses towards them were. LIS students enrolled in the 2nd semester of the AY 2007-2008 and full-time LIS professors were the respondents of the study.
A total of 108 undergraduate students and nine professors responded in the survey. Questionnaires were distributed to the students to determine their use and awareness of the popular culture materials available inside and outside the library, and how these materials affect their performance in their LIS classes. Meanwhile, a different set of questionnaires was given to the professors, which contained questions regarding their use of pop culture materials in class and how do their students respond to such materials. Descriptive statistics and frequency distribution were used in computing and analyzing the data gathered from the survey.
Based on the results of the study, most of the respondents visit the library thrice a week and frequently borrowed popular culture materials in the form of newspapers, magazines and comics, and most of these materials that they wanted to use were available in the library. Few of them access other forms (i.e., online communities, blogs) of popular culture materials in the library. They preferred magazines, books and newspapers as the types of popular culture materials to be used in class instruction.
Majority of the respondents also experienced the use of popular culture materials in their LIS classes. Their LIS professors used popular culture materials such as YouTube videos and magazine articles in their class discussions, lectures, exams and reports. Professors use popular culture materials because these materials help them make the students more awake in class and they find some of these materials relevant in class instruction, in order to illustrate concepts. The LIS professors use a combination of traditional and popular culture materials in teaching their classes because there are some concepts that could be explained clearly through the use of popular culture materials, and also to break monotony in class discussions. In turn, the respondents were more attentive and participated more in class if popular culture materials were utilized in their classes.
The researcher recommended that a comparative study between the class performances of students who frequently use popular culture materials to those who rarely use popular culture materials be conducted. The library should also include more popular culture materials that can be utilized by both the students and professors in their classes. Also, a study on the inclusion of a popular culture elective in the LIS curriculum could also be done.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines. School of Library and Information Studies -- Students; Library education -- Philippines -- Quezon City; Teaching -- Aids and devices; Effective teaching -- Philippines